Financial Performance Assessment of Large Scale Conglomerates Via Topsis and Critic Methods - Kazan, Halim; Ozdemir, Omer (International Journal of Management and Sustainability, 2014)
In this study, TOPSIS method was used to analyze financial statements of the fourteen large-scale conglomerates which are traded on Istanbul Stock Exchange (ISE). At first, the study used CRITIC METHOD to calculate nineteen financial ratios of these holdings over three periods (2009-2011), and found their financial ratio weights. TOPSIS method was applied to the nineteen financial ratio calculated, and the conglomerates were given financial performance scores in accordance with the results reached. Financial performance scores of these conglomerates were compared in order to make an inference as to their future behaviors.